Information needs of early-stage prostate cancer patients: A comparison of nine countries - (:unkn) unknown (ELSEVIER IRELAND LTD, 2010)
Background and purpose: Providing information to patients can improve their medical and psychological outcomes. We sought to identify core information needs common to most early-stage prostate cancer patients in participating countries. Material and methods: Convenience samples of patients treated 3-24 months earlier were surveyed in Canada, England, Italy, Germany, Poland, Portugal, Netherlands, Spain, and Turkey. Each participant rated the importance of addressing each of 92 questions in the diagnosis-to-treatment decision interval (essential/desired/no opinion/avoid). Multivariate modelling determined the extent of variance accounted by covariates, and produced an unbiased prediction of the proportion of essential responses for each question. Results: Six hundred and fifty-nine patients responded (response rates 45-77%). On average, 35-53 questions were essential within each country; similar questions were essential to most patients in most countries. Beyond cross-country similarities, each country showed wide variability in the number and which questions were essential. Multivariate modelling showed an adjusted R-squared with predictors country, age, education, and treatment group of only 6% of the variance. A core of 20 questions were predicted to be essential to >2/3 of patients. Conclusions: Core information can be identified across countries. However, providing the core should only be a first step; each country should then provide information tailored to the needs of the individual patient. (C) 2010 Elsevier Ireland Ltd. All rights reserved. Radiotherapy and Oncology 94 (2010) 328-333
Keywords: Early-stage prostate cancer; Patient information needs; Patient education; DECISION-MAKING; MEN; RADIOTHERAPY; SUPPORT; CARE; CHEMOTHERAPY; TRIAL; WANT